Differentially expressed proteins in gill and skin mucus of Atlantic salmon (Salmo salar) affected by amoebic gill disease - Valdenegro-Vega, VA; Crosbie, P; Andrew Bridle; Melanie Leef; Richard Wilson; Barbara Nowak (2014)
The external surfaces of fish, such as gill and skin, are covered by mucus, which forms a thin interface between the organism and water. Amoebic gill disease (AGD) is a parasitic condition caused by Neoparamoeba perurans that affects salmonids worldwide. This disease induces excessive mucus production in the gills. The host immune response to AGD is not fully understood, and research tools such as genomics and proteomics could be useful in providing further insight. Gill and skin mucus samples were obtained from Atlantic salmon ( Salmo salar ) which were infected with N. perurans on four successive occasions. NanoLC tandem mass spectrometry (MS/MS) was used to identify proteins in gill and skin mucus of Atlantic salmon affected by AGD. A total of 186 and 322 non-redundant proteins were identified in gill and skin mucus respectively, based on stringent filtration criteria, and statistics demonstrated that 52 gill and 42 skin mucus proteins were differentially expressed in mucus samples from AGD-affected fish. By generating protein–protein interaction networks, some of these proteins formed part of cell to cell signalling and inflammation pathways, such as C-reactive protein, apolipoprotein 1, granulin, cathepsin, angiogenin-1. In addition to proteins that were entirely novel in the context in the host response to N. perurans , our results have confirmed the presence of protein markers in mucus that have been previously predicted on the basis of modified mRNA expression, such as anterior gradient-2 protein, annexin A-1 and complement C3 factor. This first proteomic analysis of AGD-affected salmon provides new information on the effect of AGD on protein composition of gill and skin mucus. Future research should focus on better understanding of the role these components play in the response against infection with N. perurans .